Kajian Minyak Biji Picung Sebagai Bahan Baku Alternatif Pembuatan Biodiesel Dengan Katalis AL2O3 - Setiadi, Fydel; Bahri, Syaiful; Helwani, Zuchra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Biodiesel is an alternative energy to replace fossil fuels. It can be made by transesterification process of vegetable oils. During the process of making biodiesel usually was used NaOH or KOH as homogeneous catalyst which has the disadvantage the formation of side products such as soaps and complexity of the separation of catalyst. Therefore, in this study Al2O3 catalyst is used. This research is aimed to make biodiesel from picung seed oil, having study the effect of Al2O3 catalyst concentration on the amount of biodiesel produced, and determine the best conditions for biodiesel production. This study starts from raw material preparation which includes drying, heating, and refinement. Furthermore, extraction the picung seed oil and followed by degumming to remove impurities contained in the oil. The transesterification process of oil was done at various variation of temperature i.e 50, 60, 70 °C respectively and the various variation of catalyst concentration i.e 1%, 2%, 3% respectively at methanol of oil mole ratio 9: 1. The process was stired at speed of 200 rpm and a reaction time of 240 minutes. From the result was obtained the highest biodiesel of 97,2% at the reaction temperature of 60 °C with concentration Al2O3 catalyst 2%.Keywords : Al2O3, biodiesel, picung seed oil, transesterification